A new genus and species of chigger mite (Trombidiformes: Trombiculidae) from Loxodontomys pikumche (Rodentia: Cricetidae) in Chile - Fuente, María Carolina Silva-De La; Casanueva, María Eugenia; Salas, Lucila Moreno; González-Acuña, Daniel (Zootaxa, 2016)
The family Trombiculidae is one of the most diverse and cosmopolitan (Walter et al. 2009). In Chile, the family Trombiculidae is represented by six genera associated with reptiles: Eutrombicula Ewing; Microtrombicula Ewing; Paratrombicula Goff & Whitaker; Whartonacarus (Brennan & Jones); Diaguitacarus Stekolnikov & González-Acuña and Proschoengastia Vercammen-Grandjean and two genera associated with rodents Chilacarus Webb, Bennett & Loomis and Poliremotus Brennan & Goff (Stekolnikov & González-Acuña 2015).